AuRu/AC as an effective catalyst for hydrogenation reactions. Issue 42 (27th March 2015) - Villa, Alberto; Chan-Thaw, Carine E.; Campisi, Sebastiano; Bianchi, Claudia L.; Wang, Di; Kotula, Paul G.; Kübel, Christian; Prati, Laura
Abstract : AuRu bimetallic catalysts have been prepared by sequential deposition of Au on Ru or vice versa obtaining different nanostructures: when Ru has been deposited on Au, a Aucore –Rushell has been observed, whereas the deposition of Au on Ru leads to a bimetallic phase with Ru enrichment on the surface. Abstract : AuRu bimetallic catalysts have been prepared by sequential deposition of Au on Ru or vice versa obtaining different nanostructures: when Ru has been deposited on Au, a Aucore –Rushell has been observed, whereas the deposition of Au on Ru leads to a bimetallic phase with Ru enrichment on the surface. In the latter case, the unexpected Ru enrichment could be attributed to the weak adhesion of Ru on the carbon support, thus allowing Ru particles to diffuse on Au particles. Both structures result very active in catalysing the liquid phase hydrogenolysis of glycerol and levulinic acid but the activity, the selectivity and the stability depend on the structure of the bimetallic nanoparticles. Ru@Au/AC core–shell structure mostly behaved as the monometallic Ru, whereas the presence of bimetallic AuRu phase in Au@Ru/AC provides a great beneficial effect on both activity and stability.